Moving megaliths in the Neolithic - a multi analytical case study of dolmens in Freixo-Redondo (Alentejo, Portugal). - Boaventura, Rui (2020)
A multi-disciplinary and multi-analytical approach developed with the aim of better understanding the effort and selection criteria involved in the search for slabs used for the construction of dolmens during the Neolithic.